TINGKAT PENGETAHUAN KESEHATAN GIGI TERHADAP KEJADIAN KARIES GIGI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS KRISTEN INDONESIA ANGKATAN - Rahayu Yekti Maryanto; Donny Hiskia Turnip (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
Dental caries is the most common infectious disease in the oral cavity and is still a dental health problem in Indonesia. Lack of knowledge about dental and oral health can increase the risk of dental caries. This study aims to analyze the level of dental health knowledge on the incidence of dental caries in students of the Faculty of Medicine, Christian University of Indonesia Class of 2019. This study is a cross-sectional design study conducted from January to December 2021 with a total of 138 respondents. Knowledge of oral health and the incidence of dental caries was assessed using a questionnaire. The results of the study: there is a distribution of students who have a good level of knowledge of dental and oral health as many as 115 people (83.3%) and students who experience dental caries events are 99 people (71.7%). Bivariate analysis of Spearman correlation test and obtained p value = 0.462 > alpha value (0.05). The conclusion is that there is no relationship between knowledge of dental health and the incidence of dental caries in students of the Faculty of Medicine, Indonesian Christian University Class of 2019. Better knowledge about dental and oral health can change a better attitude in preventing dental caries. Many factors can cause dental caries that is a lifestyle of consuming sweet foods, the habit of brushing teeth after eating and before going to bed and the tooth structure is different for each person.